Education Officials’ Leadership and Management Practices that Create a Conducive Environment for Rehabilitation of Learners in a Juvenile Correctional Centre in South Africa - Maposa, Aretha Mwana (University of the Witwatersrand, Johannesburg, 2024)
Despite South Africa's policy commitments to educational rehabilitation in juvenile correctional institutions, persistent high recidivism rates reveal a disconnection between policy intentions and practical outcomes. This study addresses this challenge through a critical examination of leadership and management practices in a South African juvenile correctional secure care setting. Introducing the innovative JUmbrella Framework for Educators (JUFE), rooted in restorative justice principles, this research offers a culturally responsive model designed specifically for the unique context of South African Juvenile Correctional Institutions. Employing Constructivist Grounded Theory, the study reveals the intricate landscape of educational leadership, shedding light on current practices, their impact on juvenile offender rehabilitation, and the perspectives of education officials. Chapters 7 and 8 delve deeper into factors influencing these practices, their impact on rehabilitation, and the perspectives of education officials. The research underscores a transformative shift towards recognising the pivotal role of education in rehabilitation. However, it identifies distinct challenges and research gaps, particularly in leadership and management within this context. This study advocates for localised leadership practices tailored to address South Africa's specific challenges and culturally informed interventions that acknowledge the unique struggles faced by juvenile offenders. Additionally, it calls for initiatives promoting self- sufficiency among offenders, emphasising the importance of effective leadership and management strategies. Additionally, the study critically examines leadership and management practices, offering insights into issues of equity and epistemic justice. The findings contribute to a more comprehensive understanding of the challenges and opportunities for creating an inclusive and just educational environment within juvenile corrections. The study serves as a catalyst for transformative change in juvenile correctional education. The insights and recommendations, including the novel JUFE framework, provide valuable tools for academia and practice, aiming to shift the focus from punitive measures to transformative academic success and the successful reintegration of young offenders into society with hope and purpose.
A research report submitted in fulfillment of the requirements for a Doctor of Philosophy, In the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Juvenile correctional education; restorative justice; rehabilitation; juvenile offender learners; equity; epistemic justice; correctional justice; transformative support; JUmbrella Framework for Educators; SDG-4: Quality education